Low-carbohydrate diet improves glycemic control in patients with type 1 diabetes: a systematic review - Cruz Castillo, Juan Daniel; Juárez Rojop, Isela Esther; González Cortazar, Manasés; Nolasco Rosales, German Alberto; Gonzalez Castro, Thelma Beatriz; Marín Medina, Alejandro (Horizonte Sanitario, 2025)
Objective: This systematic review and meta-analysis aimed to evaluate the effects of LCDs on glycemic control in adults with T1D. Material and Methods: A comprehensive search was conducted in PubMed, Scopus, and Web of Science up to September 2024. Eligible studies included randomised controlled trials, cohort studies, and non-randomised interventions in adults with type 1 diabetes following LCD. Two review authors independently completed study selection, data extraction, and risk of bias assessment. Ninety-three records were discovered, of which eight research studies met the inclusion criteria. The effect of LCD on glycemic control was assessed using the standardised mean difference and 95% confidence intervals (CIs), calculated from pre- and post-intervention values. Publication bias was assessed using funnel plots and the Egger test, and heterogeneity was assessed using Cochran’s Q statistic and I² index. Results: Our results revealed significant reductions in HbA1c (point estimate: 0.79 mmol/mol; 95% CI: 0.57 to 1.02; p < 0.001) and total daily insulin dose (point estimate: 0.96 U; 95% CI: 0,67 to 1.25; p < 0.001) in adults with T1D following LCD interventions. Nonetheless, we observed no significant changes in lipid profile, anthropometric parameters, and blood pressure. Conclusions: DBCs may be effective in conjunction with drug therapy to maintain glycemic control in people with T1D. Evidence is limited by sample sizes, variability in diets, and risk of bias. Trials with appropriate methodological designs are required to validate these findings. Keywords: Low-carbohydrate diet; Type 1 diabetes; Glycemic control; HbA1c; Carbohydrate-restricted diets.